Respuestas

2013-05-05T23:52:01+02:00

1)       2x = 7+8y                    2(2x)+4y=-3

                                         2(7+8y)+4y =-3

                                           14+20y = -3                       y = 11/20               x = 57/10

2)      y = 3x - 7

                      5x-2(3x-7)=0                       x = 14              y = 35

3)      

                3x = 2y + 11                   2x+3y=16

              x = 2y + 11                      4y+22 + 3y = 16                 y = 2    x =5

                         3                                3 

4)              3x-y=3                 5x-2y=10

                 y = 3x - 3                  5x - 2(3x - 3) = 10                  x = -4       y = 9

5)    6x+y=2                     5x+4y=3

          y = 2 - 6x                 5x + 4(2 - 6x) = 3

                                                   x =5/19                       y =68/19